Performance enhancement of high-speed free space optical transmission link for the implementation of 5G and internet of things - Ai, Duong Huu; Nguyen, Van Loi; Luong, Khanh Ty; Le, Viet Truong (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Internet of things (IoT) with continuous development allows multiple devices to be connected to each other through the external environment. With that, free space optical (FSO) transmission links provide high data transmission rates, so that enhanced quality of services, that is very suitable for deployment for fifth generation (5G) and IoT. FSO is known as license free, cost effective and line-of-sight green communication technology, which is employed in various circumstances, such as high data rate connections between buildings within campus or city. This study performs enhancement of FSO link for reconfigurable intelligent surfaces (RISs) aided over free space with gamma-gamma distribution channels. The paper analyzes the performance of FSO links affected by misalignment fading, RISs aided, and link distance with the subcarrier quadrature amplitude modulation scheme. Several numerical outcomes obtained for average electrical end-to-end signal-to-noise ratio, misalignment fading displacement standard deviation and link distance are shown to illustrate the average channel capacity of systems.